Griefenow-Mewis & Bitima (Hrsg.) 2004. Oromo Oral Poetry Seen from Within - Seifert, Marc (AAeO - Afrikanistik-Aegyptologie-Online, 2005)
Griefenow-Mewis, Catherine & Tamene Bitima (Hrsg.) 2004. Oromo Oral Poetry Seen from Within. With an introduction by Wilhelm J.G. Möhlig. (Wortkunst und Dokumentartexte Band 20). Köln: Rüdiger Köppe. 91 Seiten, Broschur, € 14,80. ISBN 3-89645-276-2
Keywords: Oral Literature; Oromo; Poetry; Review